The first record and a new species of the genus Hemacroneuria from Guangxi of China (Plecoptera: Perlidae) - Mo, Raorao; Wang, Guoquan; Li, Weihai (Zootaxa, 2020)
A new species of Hemacroneuria Enderlein, 1909, H. trilobata sp. nov., is reported from Guangxi Zhuang Autonomous Region of southern China. This is the first record of Hemacroneuria from Guangxi. This new taxon is compared with related congener.